Reservoir quality management with CE-QUAL-W2/ANN surrogate model and PSO algorithm (case study: Pishin Dam, Iran) - Khodabandeh, Faranak; Dehghani Darmian, Mohsen; Azhdary Moghaddam, Mehdi; Hashemi Monfared, Seyed Arman (Arabian journal of geosciences, 2021)
Entry of various substances like phosphate and nitrate to a reservoir along with the factors such as scarcity of dissolved oxygen leads to water quality reduction. Despite these factors and lack of constant water flow into a reservoir with a long detention time, thermal stratification and eutrophication occur. This research investigates the capability of the two-dimensional CE-QUAL-W2/ANN surrogate model to simulate the quality situation in the Pishin Reservoir of Iran. For this purpose, three checkpoints with the highest average phosphate concentration in the reservoir are considered for measuring the eutrophication value using the trophic state index (TSI). In most parts of the reservoir, the concentration of phosphate as the main eutrophication indicator is up to three times the acceptable limit. Therefore, reservoir quality management is performed by controlling the amount of input phosphate from the river by optimization of the TSI with the PSO algorithm. Results demonstrate that the highest average amounts of daily allowable phosphate input to the reservoir from the first to third checkpoints are in the spring, spring, and winter, and also the least ones for these checkpoints occur in the summer, summer, and autumn, respectively. Allowable values of phosphate entrance for three checkpoints throughout the year are changed to 93%, 86%, and 59%, respectively.